'A new and hopeful type of social organism': Julian Huxley, J.G. Crowther and Lancelot Hogben on Roosevelt's New Deal. Issue 4 (22nd December 2019) - HILL-ANDREWS, OLIVER
Abstract: The admiration of the Soviet Union amongst Britain's interwar scientific left is well known. This article reveals a parallel story. Focusing on the biologists Julian Huxley and Lancelot Hogben and the scientific journalist J.G. Crowther, I show that a number of scientific thinkers began to look west, to the US. In the mid- to late 1930s and into the 1940s, Huxley, Crowther and Hogben all visited the US and commented favourably on Roosevelt's New Deal, in particular its experimental approach to politics (in the form of planning). Huxley was first to appreciate the significance of the experiment; he looked to the Tennessee Valley Authority as a model of democratic planning by persuasion that could also be applied in Britain. Crowther, meanwhile, examined the US through the lens of history of science. In Famous American Men of Science (1937) and in lectures at Harvard University, he aimed to shed light on the flaws in the Constitution which were frustrating the New Deal. Finally, Hogben's interest in the US was related to his long-standing opposition to dialectical materialism, and when he finally saw the US at first hand, he regarded it as a model for how to bring about a planned socialist society through peaceful persuasion.